El problema del mal moral y del consentimiento en la violación sexual: un análisis filosófico - Sotomayor Trelles, José Enrique (2022)
This article addresses the problem of the moral wrong present in rape. To do so, it undertakes an analysis of John Gardner's proposal on the subject. Then, identifying what Gardner calls a pure case of rape, it explores the nature and characteristics of consent as a normative transformer. To this end, it addresses the discussion, within the philosophy of action, on what is the ontology of consent. Finally, and as a consequence of holding that consent is a mental state, some problems related to the knowledge of other people’s mental states, traditionally addressed as the problem of other minds in the philosophy of mind, are raised. Some consequences for the evidentiary analysis in cases of rape crimes are drawn from this analysis.